Implemtasi Permainan Kaos Kaki Untuk Meningkatkan Karakter Kemandirian Di TK Negeri Tegal - Soleha, Siti; Husnia, Fitri; Imamah, Imamah (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to analyze the effectiveness of the educational game “Sock-Dressers” in improving the character of early childhood independence at Tegal State Kindergarten. This game uses a play while learning approach, designed to train children to wear socks independently, which also hones motor skills, decision making, and a sense of responsibility. This study used an experimental method with a pretest-posttest design involving a control group. Data was processed quantitatively through initial and final tests, and followed by observation of children's behavior in the learning process. The results showed a significant increase in the experimental group in the independence score compared to the control group. The large effect size value and high gain score support the effectiveness of this game in building independence. Behavioral observations showed that the experimental group children were more active, took initiative in completing tasks, and had higher self-confidence than the control group. Thus, the “Sock-Dressers” game makes an innovative contribution to the development of early childhood independence and is an effective learning method in supporting children's physical, social-emotional, and cognitive development.